Economic Growth Effects of the Interaction of Trade Openness and Institutions Quality: Empirical Evidence from Sub-Saharan Africa - Conteh, Salamatu Bellah; Yijun, Yuan; Sesay, Brima (International Journal of Economics and Financial Issues, 2021)
In its various publications, the International Monetary Fund (IMF) has vigorously advocated the need for reforming African trade policy from inward oriented strategies to outward oriented ones. While most countries in Africa have long accepted the reform agenda, there remains marked differences in their expected growth outcomes. This raises some skepticism about the value of trade openness on growth especially in the Sub- Saharan Africa (SSA).This paper therefore investigates how trade openness impacts growth in SSA. In order to further enrich the debate around trade policy orientation and its corresponding effects on growth, we examine the interaction effect of openness and institutions quality on growth. In doing so, panel data set were collected for a sample of 27 SSA countries covering the period 1996-2016.The study employed a dynamic panel estimation technique with a view of evaluating the relative impact of the predictors on growth. The results revealed that trade openness alone bring significant negative impact on growth performance in SSA. However, the simultaneous interaction of trade openness with institutions quality brings about positive and significant impact on growth. This confirmed that positive impact of trade openness on growth is conditional on the quality of institutions. For policy, our results imply that governments in SSA should first strengthen their institutions while adopting a gradual approach to trade liberalization. Keywords: trade openness; institutions quality; economic growth; interaction; Sub-Saharan Africa JEL Classifications: C23; C2 DOI: https://doi.org/10.32479/ijefi.10098